Joe Goldberg’s Obsessive Compulsive Personality Disorder in Caroline Kepnes’ You - Vania Hasnanisrina (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
This study analyzes Joe Goldberg's obsessive-compulsive personality disorder in You. The purpose of this study was to identify obsessive-compulsive personality disorders depicted in Joe Goldberg's character and to analyze the impact of obsessive-compulsive personality disorder from Joe Goldberg's character on himself and those around him. This study uses the theory of Theodore Millon to reveal obsessive-compulsive personality disorders in Joe Goldberg's character from You and the impact of obsessive-compulsive personality disorder on Joe Goldberg's character. The results show has an obsessive-compulsive personality disorder usually exhibits stiffness and stubbornness for example, Joe Goldberg had an obsession and control of life to the people he loved, mental and interpersonal control. The impact of Joe Goldberg's obsessed compulsive personality disorder. He will do anything for the person he loves, but in his own way, even though it intends to kill others. Keywords: personality disorder, obsessive-compulsive personality disorder.